The effect of ultrafiltered fish protein hydrolysate level on growth performance, protein digestibility and mRNA expression of PepT1 in juvenile turbot (Scophthalmus maximus L.). (18th May 2015) - Wei, Y.; Liang, M.; Mu, Y.; Zheng, K.; Xu, H.
Abstract: The intention of the study was to investigate the effect of ultrafiltered fish protein hydrolysate (UF) level on growth, feed utilization, apparent digestibility coefficients and proximal intestine peptide transporter 1 (PepT1) mRNA level for juvenile turbot ( Scophthalmus maximus L.). Experimental diets (UF‐0, UF‐5, UF‐10, UF‐15 and UF‐20) were prepared containing about 68% plant protein, and fish meal protein was, respectively, replaced by 0%, 5%, 10%, 15% and 20% UF of dietary protein. Diet PP contained about 78% plant protein, and diet CAA contained about 10% crystalline amino acid mixture. All diets were fed to seven triplicate groups of turbot (initial weight 16.05 ± 0.03 g) for 68 days. Fish fed diet UF‐10 had an increasing tendency in growth compared with diets contained UF, while dietary UF level was not significantly correlated with specific growth rate and feed intake. Feed efficiency, protein efficiency ratio and protein productive value significantly correlated with dietary UF level, and fish fed diets contained low‐level UF had higher digestibility than that diets UF‐0, PP and CAA. There was a decreasing tendency in PepT1 expression level with dietary UF level. The results indicated that low‐level UF showed a positive effect on growth and feed utilization in juvenile turbot.